The Role of Field Supervisors Through Digital Media in Guiding Students at Kampus Mengajar 6 - Mesra, Romi (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: To examine the role of field supervisors through digital media in guiding students at kampus mengajar 6 at GMIM Tonsea Lama Elementary School, focusing on their responsibilities, challenges, and impact on students' learning experiences. Methodology: This qualitative study examined Field Supervisors' activities in the Kampus Mengajar 6 program using observation and documentation methods. Data analysis followed Miles and Huberman's interactive model, involving data reduction, display, and conclusion drawing. Peer debriefing and member checking were employed to enhance credibility. The research aimed to provide insights into the supervisors' roles and responsibilities, potentially informing improvements in teacher education programs. Main Findings: The study found that Field Supervisor plays a vital role in bridging the gap between the theories learned by students on campus and the practices in the field. Through digital media, Field Supervisor can monitor student progress, provide real-time feedback, and ensure compliance with professional ethics throughout the program. Digital technology also allows for more efficient and effective coordination, helping Field Supervisor optimize mentoring despite limitations in face-to-face interaction or geographical distance. Novelty/Originality of this study: The novelty of this study lies in the in-depth exploration of the diverse roles of Field Supervisor in the Kampus Mengajar 6 program, especially in the application of educational theoretical frameworks combined with digital technology. The findings offer important recommendations for the improvement of similar programs in the future, especially in terms of optimizing the use of digital media in student guidance and supervision during the field education program.